FROM COMPLIMENT TO INSULT: THE MISUSE OF ‘SLAY’ IN THE INDONESIAN TIKTOK COMMUNITY TO DERIDE FEMININE BOYS - Doni Alfattah Reyhan Reyhan; Emy Sudarwati Sudarwati (Lire Journal (Journal of Linguistics and Literature), 2025)
This study investigates the slang terminologies use, especially 'slay', in the Western and Indonesian TikTok spheres in relation to socio-pragmatic analysis. The objective of the study is to focus on the pathways in which English words undergo changes with the passage of time and how English slang words and phrases are interpreted in the context of contemporary language, the evolution of slang terms such as 'slay' and its differing meanings between Western and Indonesian TikTok users. The study is based on socio-pragmatic theory and semantic change theory to examine how slang is used in contemporary discourse in relation to time and space, multicultural contexts, and adaptation. A qualitative approach, with particular emphasis on content analysis, is employed to identify these aspects. The TikTok creators' posts were the source of the comments and captions used for data collection. The methodology for data analysis applied to TikTok data was systematic including the identification of slang words and explaining them. TikTok users from the West and Indonesia diverge sharply in their understanding of ‘slay’. In Western TikTok, ‘slay’ is a compliment and a form of admiration, whereas in Indonesian TikTok, ‘slay’ is mostly used derisively to mock guys for being feminized and for being gay. This study showcases the extent to which English slang words can create a misunderstanding and misused across the world and with different languages.